Suture-bridge technique for tibial avulsion fractures of the posterior cruciate ligament - a biomechanical comparison. Issue 6 (28th June 2019) - Willinger, Lukas; Lacheta, Lucca; von Deimmling, Constantin; Lang, Jan; Imhoff, Andreas; Forkel, Philipp
Aims and Objectives: Tibial posterior cruciate ligament (PCL) avulsion fractures require surgical fixation in order to provide primary stability and adequate bone healing. Small fragments are common and comprise the risk to fracturing during screw fixation. Therefore, a suture-bridge configuration was developed to fixate small and multifragment fractures without the need of fragment drilling. The purpose of this study was to analyze the biomechanical properties of the suture-bridge technique compared to a well-established transtibial cortical suspension technique concerning cyclic elongation, stiffness and ultimate failure load. It was hypothesized that the suture bridge technique shows lower cyclic elongation and higher load to failure force compared to a cortical suspension button fixation. Materials and Methods: Nine fresh-frozen human cadaveric knees were biomechanically tested using an industrial testing machine (Zwick/Roell Amsler HC 10, Ulm). A standardized bony avulsion fracture (15 x 10 x 4 mm) of the tibial PCL insertion was generated. Two different techniques were used for fixation: A) 4x suture-bridge configuration (3 SwiveLock anchors, FiberTape, Arthrex Inc.) and B) 5x transtibial cortical suspension button fixation (FiberTape, Arthrex Inc). Cyclic loading was applied in 90° of flexion 500 times (10 to 100 N) to determine elongation, initial stiffness and load to failure. Students t-test for unpaired samples were used to calculate the difference of means (SPSS statistics software version 21). Statistical significance was set at a p value of < 0.05. Results: Suture-bridge technique resulted in a significant lower elongation (4.5 ± 2.9 mm) than transtibial cortical suspension button technique (11.9 ± 3.1 mm, p<0.01). Load of failure testing exhibited 319.8 ± 79.7 N in Group A and 232.6 ± 108.2 N in Group B (p=0.21). The initial stiffness at the beginning of cyclic loading was 45.0 ± 7.7 N/mm in Group A und 40.9 ± 10.0 N/mm in Group B (p=0.52). Conclusion: The novel PCL suture-bridge technique provides a significant lower construct elongation during cyclic loading and a trend towards higher load to failure in comparison to cortical suspension button fixation. As a clinical consequence, suture-bridge technique should be considered to fix small PCL avulsion fractures at the tibial insertion site.